2015
DOI: 10.1099/ijs.0.064428-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium yantingense sp. nov., a mineral-weathering bacterium

Abstract: A Gram-stain-negative, rod-shaped bacterial strain, H66(T), was isolated from the surfaces of weathered rock (purple siltstone) found in Yanting, Sichuan Province, PR China. Cells of strain H66(T) were motile with peritrichous flagella. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain H66(T) belongs to the genus Rhizobium. It is closely related to Rhizobium huautlense SO2(T) (98.1 %), Rhizobium alkalisoli CCBAU 01393(T) (98.0 %) and Rhizobium cellulosilyticum ALA10B2(T) (98.0 %). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In this study, the five rhizobacterial isolates among the six exhibited the strongest Si-solubilizing capability. The ability of bacteria to depolymerize crystalline silicate has been reported previously from diverse sources such as the soil of potassium mine tailings (Huang et al 2013), surfaces of weathered rock (purple siltstone) (Chen et al 2015), Quercus petreae oak mycorrhizal roots surroundings (Calvaruso et al 2010), soil, river water, pond sediment and talc mineral (Umamaheswari et al 2016), surfaces of weathered feldspar (Sheng et al 2008) and weathered rocks (Wang et al 2015). Diverse kinds of mineral-weathering bacterial species were reported from these studies, including Bacillus sp., Rhizobium yantingense, Bacillus globisporus, Rhizobium tropici, Pseudomonas stutzeri (Sheng et al 2008;Huang et al 2013;Chen et al 2015;Wang et al 2015;Umamaheswari et al 2016).…”
Section: Isolation Of Rhizospheric Bacteria Possessing Silicate-solubmentioning
confidence: 63%
“…In this study, the five rhizobacterial isolates among the six exhibited the strongest Si-solubilizing capability. The ability of bacteria to depolymerize crystalline silicate has been reported previously from diverse sources such as the soil of potassium mine tailings (Huang et al 2013), surfaces of weathered rock (purple siltstone) (Chen et al 2015), Quercus petreae oak mycorrhizal roots surroundings (Calvaruso et al 2010), soil, river water, pond sediment and talc mineral (Umamaheswari et al 2016), surfaces of weathered feldspar (Sheng et al 2008) and weathered rocks (Wang et al 2015). Diverse kinds of mineral-weathering bacterial species were reported from these studies, including Bacillus sp., Rhizobium yantingense, Bacillus globisporus, Rhizobium tropici, Pseudomonas stutzeri (Sheng et al 2008;Huang et al 2013;Chen et al 2015;Wang et al 2015;Umamaheswari et al 2016).…”
Section: Isolation Of Rhizospheric Bacteria Possessing Silicate-solubmentioning
confidence: 63%
“…Silicate-solubilizing bacteria can potentially release soluble silica from biogenic materials such as diatomaceous earth, rice husks, rice straw, and siliceous earth, as well as from insoluble, inorganic (Al, Ca, K, and Mg) silicates and silicate minerals such as feldspar and biotite (Wang et al, 2015;Chandrakala et al, 2019). These bacteria have been isolated from different habitats, such as rice plant rhizospheres (Kang et al, 2017;Chandrakala et al, 2019), from rice field soil samples (Vasanthi et al, 2013), weathered feldspar surfaces (Sheng and He, 2006), weathered rock surfaces (Gu et al, 2015), weathered rock (purple siltstone) surfaces (Chen et al, 2015), pond sediments, river water, soils, and talc minerals (Umamaheswari et al, 2016), potassium mine tailings (Huang et al, 2013), quercus petreae oak mycorrhizal roots surroundings (Calvaruso et al, 2010), and weathered rocks (Wang et al, 2015). Some mechanisms which SSB could utilize to release soluble silica from insoluble silicates include: (i) production of organic acids including citric, tartaric, acetic, gluconic, hexadecanoic, malic, oxalic, phthalic, oleic, heptadecanoic, and hydroxypropionic acids (Vassilev et al, 2006;Vasanthi et al, 2018), which have metal complexing properties that may bind with aluminum and iron silicates and render silicates soluble, also provide protons (H + ) for protonation for silicate hydrolysis (Duff and Webley, 1959;Avakyan et al, 1986;Drever and Stillings, 1997); (ii) inorganic acid production (i.e., oxidation of sulfur, reduction of sulfides to sulfuric acid, oxidation of ammonia to nitrates, and conversion of nitrates to nitric acid, which can act on silicates); (iii) synthesis and discharge of carbonic anhydrase that catalyzes the interconversion between carbon dioxide produced by soil microbes and water, and the dissociated ions of carbonic acid (Brucker et al, 2020), which promotes the microbial conversion of silicate minerals as observed in orthoclase degradation to kaolinite (Waksman and Starkey, 1924).…”
Section: Ssb Increase Availability Of P and Si And Their Uptake By Plantsmentioning
confidence: 99%
“…The ability to solubilize silicates (to depolymerize crystalline silicate) has been reported in various Gram-positive and Gram-negative bacteria ( Burkholderia eburnea CS4-2, Bacillus sp ., Bacillus flexus, Bacillus globisporus, B. mucilaginosus, B. megaterium and Pseudomonas fluorescens, Burkholderia susongensis sp., Rhizobium sp ., Rhizobium yantingense , Rhizobium tropici , and Pseudomonas stutzeri ) ( Malinovskaya et al, 1990 ; Lin et al, 2002 ; Liu et al, 2006 ; Vasanthi et al, 2013 , 2018 ; Chen et al, 2015 ; Gu et al, 2015 ; Wang et al, 2015 ; Umamaheswari et al, 2016 ; Kang et al, 2017 ; Chandrakala et al, 2019 ).…”
Section: Ssb Increase Availability Of P and Si And Their Uptake By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizobium yantingense H66 and Rhizobium etli CFN42 (the similarity of the 16S rRNA gene sequences between Rhizobium yantingense H66 and Rhizobium etli CFN42 is 95%) were used to compare the modes and mechanisms of mineral weathering. The mineral-weathering strain H66 was isolated from the surfaces of weathered purple siltstone and was determined to be a new Rhizobium species (Rhizobium yantingense) (22). The concentrations of Si, Al, and Fe in Bushnell-Haas medium (BHm) containing 5.0% (wt/vol) biotite (50-to 150-m size fraction) and incubated for 7 days at 28°C increased 2.7-to 3.7-fold, 2.5-to 3.5-fold, and 9.6-to 17-fold, respectively, in the presence of strain H66 compared to those of the uninoculated controls.…”
Section: Methodsmentioning
confidence: 99%